Cooperation and Importance of School and Family on Values Education - Yaşaroğlu, Cihat (European Journal of Multidisciplinary Studies, 2016)
Values are one of the basic identifier of personality traits and are not innate but acquired by training. Although values can be taught in all stages of life, values education gain importance in childhood because personality takes shape in it. Values education firstly begins in family, than continues at educational institutions. Basic values are acquired respectively by taking parents as role models and education at schools. For the strengthened personality traits, the values thought at whole life must be coherent. Especially consistency of school and family that is important on children personality highlights for values education. If there is no consistency between the values that students learned or witnessed in the school and in the family, then conflicts are occurred and these situations cause personality disorders. This research aims to investigate the importance of family and school consistency in values education and how it should be during fundamental/primary education level. Considering findings, proposals were developed for family and school in values education.
Keywords: Values education, family, schools, consistency, character education